2022
DOI: 10.1038/s41594-022-00812-9
|View full text |Cite
|
Sign up to set email alerts
|

The structure-specific endonuclease complex SLX4–XPF regulates Tus–Ter-induced homologous recombination

Abstract: Vertebrate replication forks arrested at an interstrand DNA crosslink (ICL) can engage the Fanconi anemia (FA) pathway of ICL repair. The FANCP product, SLX4, binds the FANCQ/XPF/ERCC4-ERCC1 endonuclease, which incises bidirectionally arrested forks to 'unhook' the ICL. The resulting double strand break (DSB) is repaired by homologous recombination (HR). Whether this mechanism operates at replication blocks other than ICLs is unknown. Here, we study the role of mammalian SLX4 in HR triggered by a site-specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…For example, SLX1 is catalytically inactive until it binds the conserved C-terminal domain (CCD) domain of SLX4, after which it is competent to cleave many types of branched DNA structures [10,[12][13][14]. Similarly, SLX4 stimulates XPF-ERCC1 to cleave replication forks that stall at protein-DNA adducts or interstrand crosslinks [18,19]. When cells enter mitosis, phosphorylation of the SLX4 scaffold triggers the recruitment of MUS81-EME1, leading to the formation of a tri-nuclease complex called SMX (for SLX1-SLX4, MUS81-EME1, and XPF-ERCC1) [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, SLX1 is catalytically inactive until it binds the conserved C-terminal domain (CCD) domain of SLX4, after which it is competent to cleave many types of branched DNA structures [10,[12][13][14]. Similarly, SLX4 stimulates XPF-ERCC1 to cleave replication forks that stall at protein-DNA adducts or interstrand crosslinks [18,19]. When cells enter mitosis, phosphorylation of the SLX4 scaffold triggers the recruitment of MUS81-EME1, leading to the formation of a tri-nuclease complex called SMX (for SLX1-SLX4, MUS81-EME1, and XPF-ERCC1) [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Early clues about the scaffold function of mammalian SLX4 came from bioinformatics and affinity purification coupled to mass spectrometry (AP-MS) experiments, which revealed that SLX1, MUS81-EME1, and XPF-ERCC1 bind distinct regions of SLX4 (Figure A). Subsequent biochemical studies revealed that SLX4 activates and regulates its endonuclease partners. For example, SLX1 is catalytically inactive until it binds the conserved C-terminal domain (CCD) of SLX4, after which it is competent to cleave many types of branched DNA structures. , Similarly, SLX4 stimulates XPF-ERCC1 to cleave replication forks that stall at protein–DNA adducts or interstrand crosslinks. , When cells enter mitosis, phosphorylation of the SLX4 scaffold triggers the recruitment of MUS81-EME1, leading to the formation of a tri-nuclease complex called SMX (for S LX1-SLX4, M US81-EME1, and X PF-ERCC1). , Notably, SLX4 binding to MUS81-EME1 stimulates the cleavage of branched DNA structures that represent replication and recombination intermediates . The current model is that SMX provides cells with a multifunctional nuclease that removes joint molecules prior to cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Biallelic inactivation of SLX4 underlies complementation group P of Fanconi anemia (27, 28 ), an inherited disease associated with congenital abnormalities, pancytopenia and cancer proneness ( 29 ). SLX4 associates with multiple DNA repair factors including the structure-specific endonucleases (SSEs) XPF-ERCC1, MUS81-EME1, and SLX1 to repair interstrand DNA crosslinks, drive the resolution of Holliday junctions, promote DNA repair synthesis at common fragile sites and/or ensure telomere maintenance ( 3040 ). Furthermore, SLX4-XPF promotes homologous recombination at a replication fork barrier caused by tightly DNA-bound proteins ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…SLX4 associates with several DNA repair factors including the structure-specific endonucleases (SSEs) XPF-ERCC1, MUS81-EME1, and SLX1 to repair DNA interstrand crosslinks, resolve Holliday junctions, ensure telomere maintenance, and maintain stability of common fragile sites [42][43][44][45][46][47][48][49][50][51][52][53] . Recent evidence indicates that at a replication fork barrier caused by tightly DNA-bound proteins, SLX4-XPF promotes the recruitment of DNA damage response factors and DNA repair by homologous recombination 54,55 . SLX4 and XPF deficient cells are hypersensitive to DNA methyltransferases and topoisomerase 1 DNAprotein crosslinks (DPCs) 54,56,57 , but how SLX4-XPF mechanistically promotes the processing of DPCs remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation